The Effect of Implementation and Socialization of E-Invoice 3.0 on Compliance of Taxable Entrepreneurs For Reporting Value Added Tax Annual Notice - Vita Aprilina; Muhammad Sugeng Bariyanto (Future Science, 2022)
The purpose of this study is to analyze the effect of the implementation of e-invoice 3.0 and the socialization of e-invoice 3.0 on the compliance of taxable entrepreneurs for reporting Value Added Tax annual report in the Bekasi Region, especially in KPP Pratama Cibitung. This study uses a quantitative method and the type of data used by the researcher is primary data collected by data collection techniques through questionnaires distribution also through Google Form.the data collected was 121 respondents and processed into 97 respondents according to predetermined criteria. The data analysis method used is multiple regression analysis. Based on the results of respondents' answers through a questionnaire and processed using the SPSS 25 application, it can be concluded that the application of e-inovice 3.0 has a positive effect on compliance with taxable entrepreneurs, and the socialization of e-invoice 3.0 has a positive effect on compliance with taxable entrepreneurs.